Chess players [videorecording (DVD)] = Shatranj ke khilari - Ray, Satyajit, 1921-1992 (Devki Chitra Productions ; Distributed by Kino on Video, 2006)
The kingdom of Oudh has a gently decadent Nawab (king), who is busy being a poet, composer, singer, dancer, and choreographer, but not a ruler. Mirza and Mir are old friends, living in the capital city off ancestral wealth and taxes on their lands. As the king is obsessed with his artistic endeavors, the friends are obsessed with shatranj (chess). In 1856, the East India Company sends General Outram, the British Resident of Lucknow, to take over the kingdom, under the charge of misrule. The king dithers, the friends play chess. British troops march into the city; the king surrenders without a fight, and the friends remove to a distant village so they can play in peace.